Evaluation of oxygen concentration on low-temperature oxidation kinetics of long-flame coal. (October 2022) - Zhao, Jingyu; Lu, Shiping; Song, Jiajia; Zhang, Yuxuan; Zeng, Qiang; Shu, Chi-Min
Abstract: Oxygen concentration is the vital environmental factor affecting the evolution of coal spontaneous combustion. Long-flame coal was heated from 30 to 800 °C at different oxygen concentrations (3, 5, 9, 13, 17, and 21 mass%) and heating rates (2.0, 5.0, 10.0, and 15.0 °C/min). The thermal reaction process was explored and analyzed. The effects of oxygen concentration on characteristic temperature and related parameters were assessed. The effects of heating rate and oxygen concentration on characteristic temperature and related parameters were evaluated. Under the condition of oxygen deficiency, the oxidation rate of coal was low, it took more time to consume the active groups in a given quality coal, and the increase of oxygen concentration had a strong positive effect on early and late combustion. The apparent activation energy ( E a ) increased and decreased the conversion degree of oxygen absorption (mass gain) and high-temperature combustion stage, respectively. With the decrease of oxygen concentration, E a in each stage decreased. These results contribute to the understanding of the evolution of coal fires in oxygen-lean environments. Highlights: The mechanism of oxygen concentration on coal spontaneous combustion characteristics at low heating rate was determined. The phase characteristics of coal oxygen-poor oxidation at a low heating rate were characterized. The kinetics of oxygen-poor oxidation of coal was investigated.